Does reduced erythrocyte C3b receptor (CR1) activity contribute to the pathogenesis of yersinia triggered reactive arthritis?. Issue 1 (January 1992) - Lahesmaa, R; Eerola, E; Toivanen, A
Abstract : Erythrocyte C3b receptor (CR1) activity was measured in 27 patients with yersinia triggered reactive arthritis and in 151 control subjects, including 36 patients with uncomplicated yersiniosis and 115 healthy subjects. CR1 was measured by the immune adherence haemagglutination method. Patients with yersinia triggered reactive arthritis had reduced levels of CR1 compared with the controls. This difference was mainly due to the finding that five out of six HLA B27 negative patients with arthritis had decreased CR1 activity. Such a quantitative difference may contribute to the pathogenesis of reactive arthritis by affecting the clearance of immune complexes.